2022
DOI: 10.1007/s00246-022-02934-9
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Negative Career Impact of the COVID-19 Pandemic on Female Pediatric Cardiologists in the Northeast United States

Abstract: The COVID-19 pandemic has had a dramatic impact on practicing physicians, with effects in clinical practice, academic pursuits, research endeavors, and personal lives. Women in medicine have been uniquely impacted. We examined the impact of the pandemic on the careers of pediatric cardiologists in the Northeast with an anonymous online survey. Participants reported demographic data, information on work hours, administrative burden, career satisfaction, academic productivity, and burnout. We approached 490 card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(23 reference statements)
0
3
1
Order By: Relevance
“…For physician faculty, the combination of research restrictions with increased clinical workload may have especially hindered participation in research and scholarly activity, regardless of the topic. Although recent survey studies have found that physician faculty self-reported decreases in academic productivity, 28,29 our study found that among US medical schools, most of the institutions were able to sustain growth in the number of publications from 2019 through 2021. Furthermore, we identified structural factors related to research capacity, faculty diversity, and the impact of the pandemic that may have contributed to differing trends in scholarly productivity among medical schools during this time.…”
Section: Discussioncontrasting
confidence: 62%
“…For physician faculty, the combination of research restrictions with increased clinical workload may have especially hindered participation in research and scholarly activity, regardless of the topic. Although recent survey studies have found that physician faculty self-reported decreases in academic productivity, 28,29 our study found that among US medical schools, most of the institutions were able to sustain growth in the number of publications from 2019 through 2021. Furthermore, we identified structural factors related to research capacity, faculty diversity, and the impact of the pandemic that may have contributed to differing trends in scholarly productivity among medical schools during this time.…”
Section: Discussioncontrasting
confidence: 62%
“…Dr. Smith’s pregnancy was unremarkable with the exception of significant additional fatigue. The COVID-19 pandemic further aggravated her overall health and sense of well-being (Laraja et al, 2022 ).…”
Section: Clinical Vignettementioning
confidence: 99%
“…Burnout, first described in 1974 and expanded over time, explains a multidimensional stress syndrome consisting of mental fatigue (emotional exhaustion), negative perceptions and feelings about clients or patients (depersonalization), and reduced perceptions of professional competence (Maslach & Jackson, 1981 ). While all professional healthcare staff can be vulnerable to burnout, these concerns were aggravated during the COVID-19 pandemic and reinforced that women in medicine face unique additional professional challenges (Laraja et al, 2022 ). More recently, engagement has been appreciated as a critical component of staff retention, financial success, patient safety, patient quality, and career satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges have contributed to increased levels of burnout and decreased levels of career satisfaction among academic physicians. [2][3][4][5] Even as restrictions on in-person meetings were lifted by institutions, many faculty preferred meetings to remain virtual and hence the erosion of faculty relationships created by the pandemic has the potential to continue if left unaddressed.…”
Section: Introductionmentioning
confidence: 99%